RELIGIOUS RESPONSES TO CLIMATE CHANGE AND ENVIRONMENTAL DEGRADATION - Shaikh Mohd. Saifuddeen Shaikh Mohd. Salleh (Khayra Ummah Series (No.6/9), 2022)
This volume is part of the Khayra Ummah series, being itself the culmination of a sequence of colloquium of several themes organised by IKIM. The issues addrressed in this series are : Islamic economics; Islamophobia;governance;moral deterioration;disruptive technology;the Islamic state and society; environmental degradation; and the Islamic mind.